Arginylated calreticulin at plasma membrane increases susceptibility of cells to apoptosis - López Sambrooks, Cecilia (2012)
Post-translational modifications of proteins are important for the regulation of cell fate and functions; one of these post-translational modifications is arginylation.Wehave previously established that calreticulin (CRT), an endoplasmic reticulum resident, is also one of the arginylated substrates found in the cytoplasm. In the present study, we describe that arginylated CRT (R-CRT) binds to the cell membrane and identified its role as a preapoptotic signal.Wealso show that cells lacking arginyltRNA protein transferase are less susceptible to apoptosis than wild type cells. Under these conditions R-CRT is present on the cell membrane but at early stages is differently localized in stress granules. Moreover, cells induced to undergo apoptosis by arsenite show increased R-CRT on their cell surface. Exogenously applied R-CRT binds to the cell membrane and is able to both increase the number of cells undergoing apoptosis in wild type cells and overcome apoptosis resistance in cells lacking arginyl-tRNA protein transferase that express R-CRT on the cell surface. Thus, these results demonstrate the importance of surface R-CRT in the apoptotic response of cells, implying that post-translational arginylation of CRT can regulate its intracellular localization, cell function, and survival.